Evaluation of Sentinel Node Biopsy in Locally Advanced Breast Cancer Patients Who Become Clinically Node-Negative after Neoadjuvant Chemotherapy: A Preliminary Study. (12th October 2011) - Thomas, Shaji; Prakash, Apurva; Goyal, Vinay; Popli, Manju Bala; Agarwal, Shilpi; Choudhury, Monisha
Abstract : Introduction . Controversy continues over the appropriate timing of sentinel lymph node (SLN) biopsy in locally advanced breast cancer (LABC) patients receiving neoadjuvant chemotherapy. We evaluated the feasibility and accuracy of SLN biopsy in LABC patients with cytology-proven axillary nodal metastasis who become clinically node-negative after neoadjuvant chemotherapy. Materials . 30 consecutive patients with LABC, who had become clinically node-negative after 3 cycles of neoadjuvant chemotherapy, were included in the study. They were then subjected to SLN biopsy, axillary lymph node dissection, and breast surgery. Results . Sentinel nodes were successfully identified in 26 of the 30 patients, resulting in an identification rate of 86.67%, sensitivity of 83.33%, false negative rate of 20%, negative predictive value of 72.73%, and an overall accuracy of 88.46%. No complications were observed as a result of dye injection. Conclusions . SLN biopsy is feasible and safe in LABC patients with cytology-positive nodes who become clinically node-negative after neoadjuvant chemotherapy. Our accuracy rate, identification rate, and false negative rate are comparable to those in node-negative LABC patients. SLN biopsy as a therapeutic option in LABC after neoadjuvant chemotherapy is a promising option which should be further investigated.